'It's all bad news': the first 3 months following a diagnosis of malignant pleural mesothelioma (MPM). (1st April 2011) - Arber, A; Spencer, L; Parker, A
Abstract : Abstract: MPM is a rare cancer with a rising incidence associated with asbestos exposure. The disease is invariably fatal with many people dying within a year of diagnosis, with typical survival of only 7–10 months. Aims: This study explores how patients with malignant pleural mesothelioma (MPM) cope during the first 3 months following diagnosis. Methods: The study uses narrative interviews with 10 people diagnosed with MPM during the first 3 months following diagnosis, from two hospital trusts in the UK. Data was analysed using the constant comparative method to identify common categories and then themes. Results: A key theme that emerged from the data was the feeling of hopelessness associated with MPM in that it is 'all bad news'. Participants describe suffering distress around how their disease will progress. They avoid seeking information as everything they hear about the disease is so negative and there are few effective treatments available. The study identifies a lack of psychosocial and emotional support for people with MPM leading to a sense of isolation, fear and uncertainty about the future and the progress of the disease. Participants report receiving little help and advice related to significant symptoms such as sweating, pacing themselves and coping with breathlessness on exertion. Conclusion: Few patients received an early referral to specialist palliative care. A palliative rehabilitative approach is recommended early on following diagnosis to support hope and manage the many physical symptoms and emotional distress.